The elastic-plastic response of Hadfield steel under indentation test - Kaya, Utku (Univerzita Pardubice, 2014)
Headfield steel is currently widely used for cast railway frogs and railway application. Because of its excellent work hardening capability, suitable strength and high toughness. Explosive hardening technique can obviously increase the hardness of metals by severe plastic deformation caused by the shock wave. A few previous research reports on the explosion hardening technique of the Hadfield manganese can be found only. Norman first reported an explosion hardening technique in 1955and got a patent for this technique. [1] In this paper, Rolling contact test was performed for with vs without explosive hardness steel. Sample from rolling contact test was cut out and made metallographic analysis. Dislocations and white etching layer was observed. Several Indentation test were performed with cylindrical and Vickers indenter. Beside this, Martens hardness value (HM) was measured from surface to inner layer.